Identification of Clinical Infections of Leishmania Imported into Australia: Revising Speciation with Polymerase Chain Reaction-RFLP of the Kinetoplast Maxicircle - Kaufer, Alexa (Am J Trop Med Hyg, 2019)
Leishmaniasis is a vector-borne disease caused by protozoan parasites of the Leishmania genus. In Australia, leishmaniasis is an imported disease that is presenting itself at increased rates because of international travel, the influx of immigrants, and deployment of military operations to endemic regions. Although Leishmania species are morphologically indistinguishable, there is a strong correlation between some causative species of leishmaniasis and the subsequent response to the treatments available and patient outcome. Consequently, identification of the infective species is imperative as misidentification can result in the administering of an ineffective drug. The aim of this study was to develop a simple diagnostic tool with high sensitivity and specificity, which is capable of detecting the presence of the parasite and accurately differentiating the causative species in question. Using the advantageous properties of the maxi-circle kinetoplast DNA, a polymerase chain reaction (PCR)-restriction fragment length polymorphism (RFLP) targeting the ND7 gene was developed for the analysis of imported cases of human leishmaniasis in Australia. Designed as a dual analysis, concurrent PCR of Leishmania maxi-circle DNA and digestion with two separate enzymes (NlaIII and HpyCH4IV), this study provides an appraisal on 24 imported cases of leishmaniasis between 2008 and 2017. Five Leishmania species were reported, with members of the Viannia subgenus being the most common. The implementation of novel diagnostic procedures for leishmaniasis such as the one reported here is needed to establish a gold standard practice for the diagnosis and treatment of leishmaniasis.